Pelatihan Perencanaan Keuangan Ala Nabi Yusuf Alaihissalam For Kids Bagi Santri Pesantren Ramadhan Masjid Al-Iqdam - Asiroch Yulia Agustina; Nur Khayin Muhdlor; Masfiatun; Ahmad Faishal Zindan (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
This Community Service activity aims to introduce the basic concepts of financial systems and wealth management in accordance with Islamic teachings through an innovative approach that integrates the story of Prophet Yusuf Alaihissalam as a learning medium tailored for children. The novelty of this activity lies in the presentation of Islamic financial literacy material, which is not only delivered theoretically but also packaged through the exemplary lessons found in the Quranic story, making it easier to understand, more relevant, and capable of fostering religious awareness at the same time. The activity was held at the Main Hall of Masjid Jami’ Al-Iqdam, Lenteng Agung, South Jakarta, as part of the Ramadhan Islamic Boarding School series of events. This program was designed based on the urgent need to instill Islamic economic values from an early age, so that the younger generation understands that managing finances is not merely a worldly matter, but also a form of worship and a trust that must be accounted for before Allah SWT. The implementation methods included interactive lectures, inspirational storytelling, and hands-on simulation exercises. The material covered the true nature of wealth, the importance of saving, future planning, as well as the principles of justice and honesty, all exemplified by Prophet Yusuf Alaihissalam. The results showed high enthusiasm among participants and a significant improvement in their understanding. This improvement was measured using pre-test and post-test instruments consisting of 12 questions based on 4 indicators, with an average increase in understanding reaching 68.3%